Distinguishing eastern North American forest moth pests by wing-scale ultrastructure: potential applications in paleoecology - Kristen J. Milbury; Les C. Cwynar; Sara Edwards (Canadian Science Publishing, 2019)
The use of fossil moth wing scales has recently been introduced as a new method to reconstruct population histories of lepidopterans and provide a proxy for insect disturbance. We investigated the potential for using wing-scale ultrastructure to distinguish between the five most common outbreak species of moth pests in eastern North America: spruce budworm (Choristoneura fumiferana Clemens), hemlock looper (Lambdina fiscellaria Guenée), forest tent caterpillar (Malacosoma disstria Hübner), blackheaded budworm (Acleris variana Fernie), and jack pine budworm (Choristoneura pinus Freeman). Using scanning electron images of scales, we made qualitative and quantitative comparisons of morphological traits at the ultrastructural level. We found that hemlock looper and eastern blackheaded budworm scales could be categorically separated from each other and from the three other species. We developed a quadratic discriminant function using measurements of ultrastructure traits that distinguishes scales of the three remaining species with an overall accuracy of 66%. We found that forest tent caterpillar could be well separated based on these traits, but we were less confident in distinguishing the closely related jack pine and spruce budworm. Our method offers potential advantages in scale identification for future studies in paleoecology, while providing the additional advantage of not requiring intact, unfolded, and undamaged scales.